The Efficacy of Clove (Syzygium aromaticum) Decoction in Alleviating Gout Pain in the Elderly: A Systematic Literature Review - Oktaviani, Sophia; Rosalina, Dela Gita; Nurazizah, Tsaniya; Purwati, Ayu Endang; Setiawan, Henri; Hidayat, Nur; Rahman, Irfan Ali (Genius Journal, 2025)
Introduction: Gout pain is a common issue among the elderly, caused by the accumulation of uric acid crystals in the joints, leading to discomfort and limited mobility. Clove (Syzygium aromaticum), known for its anti-inflammatory and analgesic properties, has been studied as a potential natural treatment for alleviating gout pain. Objective: This study aims to analyze the effectiveness of clove (Syzygium aromaticum) decoction in reducing gout pain among the elderly. Method: A systematic review search was conducted across four journal databases: PubMed, ProQuest, Garuda, and JSTOR, covering the period from 2019 to 2024. The population involved in the studies consisted of elderly individuals diagnosed with gout. The intervention analyzed in this review was the administration of clove decoction, while pain as the primary outcome was measured using the Numerical Rating Scale (NRS). The uric acid levels, as a secondary outcome, were assessed using a GCU meter. Two to three independent reviewers conducted the search, selection, extraction, and quality assessment of the identified articles. The selection process followed the PRISMA flowchart standards, while the quality of the articles was evaluated using the CASP checklist. The extracted data included key aspects such as author, intervention, facilitators, setting, number of sessions, duration, methods or media used, as well as the topics discussed in each study. Result: Of the five articles identified, a total of 95 participants were involved. The administration of clove decoction significantly reduced pain intensity due to its higher eugenol content, which was given orally (consumed) and via warm compress. The intervention was administered for 5-7 days, while the warm compress was applied for 15-20 minutes. The duration of this intervention allowed sufficient time for the eugenol content in cloves to act as an anti-inflammatory and analgesic, resulting in a more optimal therapeutic effect. Conclusion: The administration of clove decoction is a non-pharmacological therapy that demonstrates a significant impact in reducing gout pain. It may serve as a supportive alternative in pain management, reducing the use of analgesics, and improving the quality of life with minimal side effects.